Orthopaedic examination, evaluation & intervention : - Dutton, Mark (McGraw-Hill, 2005)
The perfect companion to Dutton’s Orthopaedic Examination, Evaluation and Intervention. Also serves as a handy pocket reference for any physical therapist needing a ready source of information at the point of care.